A proposed digital control system using a mobile application for municipal solid waste management in South Africa - Adeleye Ayoade Adeniran; Winston Shakantu; Emma Ayesu- Koranteng (Diponegoro University, 2022)
The generation and handling of waste are significant challenges to developing nations like South Africa. Studies show that improper disposal of waste results in un-aesthetic, unhygienic and other health-related issues in developing nations. In addition, waste is usually generated as a result of daily activities of humans and animals; and in developing countries, the generation of waste per unit of output is much higher than that of the developed countries; and coupled with this is the challenge of effectively integrating a solid waste management system in South Africa. This paper reviewed and analysed literature to provide a theoretical framework for understanding waste and the role that digitisation could play in its management. The research shows that sustainable and digital waste monitoring can be achieved in South Africa if there is a proper plan, effective environmental policy and cooperation between the government, private sector, partners and the citizens. Moreover, if waste handling can be harnessed into a local economic development opportunity, its handlers and generators could be persuaded to manage the waste differently and properly. This would, further, create employment and revenue generation opportunities as well as a greener environment.